Poverty, women’s empowerment and social entrepreneurship among b40 urban women in Malaysia = Pobreza, empoderamiento de las mujeres y emprendimiento social entre las mujeres urbanas b40 en Malasia - Rokis, Rohaiza; Basir, Norasikin; Syed Hussien, Sh Fatimah Alzahrah; Muhammad Fauzi, Fatin Nadhirah (Universidad del Zulia, 2018)
The current study investigates the level of awareness and intention on social entrepreneurship among B40 women in urban areas. Data are obtained through set structured interview items and analyzed ith the assistance of Atlas.ti 8. The initial main finding indicates that B40 urban women have no indicative understanding of social entrepreneurship even after layman terms and contexts are applied. In conclusion, as long as B40 urban women believe that they are generating a positive return to society, social entrepreneurship is possible. It is noted that social entrepreneurship can be in major community development projects as well as health care.